Green Online Retailer Towards Brand Sustainability - Hutomo, Edwin Joyo; Buana, Yud; Kurniawan, Yohanes Jhony (Jayapangus Press, 2021)
The shift in shopping methods from physical (offline) stores to virtual (online) stores has crystallized even more. Gradually the shift allows consumers to feel easy and comfortable in respect to buying products by online methods. This earliness paradigm shift becomes interesting if it becomes a topic of the research regarding the possibility of its sustainability in the triple bottom line. The clarity of the consumer's perspective on brand sustainability in terms of the main three pillars is being tested to clarify the roots of the paradigm by becoming a hypothesis in this research. The hypothesis was tested using Structural Equation Modeling on the answers of 278 respondents to identify the significant path. The findings are quite surprising so that entrepreneurs require to put forward the sustainability side of their brand. Future research should be aimed at adding more detailed factors related to the need for the process of achieving sustainability.